VD_FINDINFO Jug / 2011 / 250 vom 16. Juni 2011 - VD Tribunal cantonal (2011)
ACCIDENT DE LA CIRCULATION, CIRCULATION EN SENS INVERSE, RÈGLE DE LA CIRCULATION | 106 CP, 31 al. 1 LCR, 34 al. 1 LCR, 51 al. 1 LCR, 90 ch. 2 LCR, 91 al. 1 LCR, 91a LCR, 92 al. 1 LCR, 93 ch. 2 LCR